2012
DOI: 10.1002/ejic.201200442
|View full text |Cite
|
Sign up to set email alerts
|

PtIIand PdIIComplexes with atrans‐Chelating Bis(pyridyl) Ligand

Abstract: An atropisomeric bis(pyridyl) chelate ligand bis{3,3′‐[N‐Ph‐2‐(2′‐py) indolyl]} (bpib) has been found to readily form trans‐chelating PdII and PtII complexes. Two such complexes, Pt(bpib)Cl2 and Pd(bpib)Cl2 have been isolated and their structures were determined by single‐crystal X‐ray diffraction analysis. Both Pt(bpib)Cl2 and Pd(bpib)Cl2 have a chiral structure with C2 symmetry. Pt(bpib)Cl2 displays a long‐lived phosphorescence with λem = 595 nm in a frozen CH2Cl2 solution at 77 K. To examine the potential u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“… 24 There are rather more nine-membered rings where both donors to the metal are nitrogen. In some of the crystal structures of these κ 2 N donors the donors span trans 25 coordination sites, some cis 26 and there is one example where a change from trans to cis occurs upon addition of CO. 27 The formation of the eight-membered linkage that becomes the nine-membered metallacycle from two equal sized rings does not appear to have been seen before with two different cyclometallated ligands (as in the phosphine and pyridine reported here), but has been seen with two identical ligands. Thus, reported examples include the coupling of two cyclometallated phenylpyridines to give a nine-membered metal containing ring, 25a , 27 and a similar coupling but where the coupled product detaches from the metal.…”
Section: Resultsmentioning
confidence: 99%
“… 24 There are rather more nine-membered rings where both donors to the metal are nitrogen. In some of the crystal structures of these κ 2 N donors the donors span trans 25 coordination sites, some cis 26 and there is one example where a change from trans to cis occurs upon addition of CO. 27 The formation of the eight-membered linkage that becomes the nine-membered metallacycle from two equal sized rings does not appear to have been seen before with two different cyclometallated ligands (as in the phosphine and pyridine reported here), but has been seen with two identical ligands. Thus, reported examples include the coupling of two cyclometallated phenylpyridines to give a nine-membered metal containing ring, 25a , 27 and a similar coupling but where the coupled product detaches from the metal.…”
Section: Resultsmentioning
confidence: 99%
“…The Pd-catalyzed C–H acetoxylation of benzene was originally reported in the 1970s using simple Pd salts and oxidants such as K 2 Cr 2 O 7 and K 2 S 2 O 8 . While these early studies provided proof-of-principle for the feasibility of this transformation, the catalyst turnover numbers (TON) were too low for practical utility (typically ranging between <1 and 7). In 1996, Crabtree reported that the combination of Pd­(OAc) 2 as catalyst and PhI­(OAc) 2 as oxidant afforded dramatically improved results, with up to 127 turnovers in the C–H acetoxylation of naphthalene . More recently, our group has demonstrated that the rate and TON of Crabtree’s reaction can be increased dramatically through the use of pyridine (pyr) as a supporting ligand .…”
Section: Introductionmentioning
confidence: 99%
“…Diphosphine ligands have played an important role in organometallic chemistry, especially because of their ability to support metal complexes that are highly active in catalysis . Most bidentate ligands have a strong preference toward cis coordination, although examples of trans-chelating ligands are known. While cis-chelating diphosphines, with bite angles of ∼90°, have been employed for many decades, the first ligand designed to coordinate trans to a metal center dates from 1976. Known as TRANSPHOS, it is still arguably the diphosphine that received the most attention among trans-spanning ligands .…”
Section: Introductionmentioning
confidence: 99%